Competitiveness and Impact of Government Policies on Beef Cattle Business in East Kolaka District, Indonesia: A Policy Analysis Matrix Approach - Abadi, Musram; Nafiu, La Ode; Rezky, Muhammad; Gerhana, Gerhana (Buletin Peternakan, 2025)
Beef is one of the main food commodities, so to realize beef self-sufficiency, the government has made many policies to realize the beef self-sufficiency program.The objective of this study was to analyze the competitiveness and impact of government policies on beef cattle in East Kolaka District, Southeast Sulawesi Province. This research was conducted in East Kolaka Districtin 2024, a total of 120 beef cattle farmers weresurveyed using systematic purposive sampling and data were analyzed using the Policy Analysis Matrix (PAM) an economic tool for evaluating competitiveness and policy effects. The respondents were obtained by applying systematic purposive sampling with survey method and analyzed with PAM. The results showed that beef cattle farming in East Kolaka Districtispersonally and socially profitable. This explains that beef cattle farming is still profitable for farmers even without government policy. This business also has competitiveness both competitively and comparatively. This can be seen from the Domestic Resource Cost Ratio (DRC) svalue of 0.59 and Private Cost Ratio (PCR) of 0.81. Government policies on outputs and inputs of beef cattle business in East Kolaka District reduce incentives for producers, are ineffective in protecting production and cause higher production costs compared to potential profits without these policies